Using an interprofessional decision-making model to determine the level of collaborative decision-making in a virtual learning environment: Using an interprofessional decision-making model - Beckingsale, Louise; Morgan, Sonya; Duffull, Stephen; Hider, Phil; McDermott, Louise; Peterson , Aynsley; McKinlay, Eileen (The Journal of Practice Teaching and Learning, 2024)
Medicine and pharmacy students benefit from interprofessional education that supports the learning of collaboration skills for medicines management decision-making. However, if and how students undertake collaborative decision-making processes in interprofessional student teams has not been investigated. The aim of this study was to determine the level to which pharmacy and medical students collaborate to make medicines management decisions in a learning activity. Eight pharmacy and 13 medical students completed a 9-item survey to evaluate a interprofessional learning activity. A secondary analysis of survey data using a deductive approach, according to the Model of Interprofessional Decision-Making was undertaken. Different levels of collaboration were identified in the students’ responses ranging from the first and lowest level in the model, Individual Decision Making, to the fourth and highest level, Shared Decision. Most student responses were categorised as level three-Deliberation. Findings from this study indicate that pharmacy and medical students collaborate to different levels with each other to make patient care decisions. Further examination is required to see if this is usual variation or related to the design of the learning activity.